2013
DOI: 10.1371/journal.pone.0070430
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Proliferating Cell Nuclear Antigen and Its Protein Interactions Induces Apoptosis in Multiple Myeloma Cells

Abstract: Multiple myeloma is a hematological cancer that is considered incurable despite advances in treatment strategy during the last decade. Therapies targeting single pathways are unlikely to succeed due to the heterogeneous nature of the malignancy. Proliferating cell nuclear antigen (PCNA) is a multifunctional protein essential for DNA replication and repair that is often overexpressed in cancer cells. Many proteins involved in the cellular stress response interact with PCNA through the five amino acid sequence A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
158
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(174 citation statements)
references
References 34 publications
(59 reference statements)
14
158
0
2
Order By: Relevance
“…For example, in mature non-proliferating neutrophils, PCNA is exclusively located in the cytosol where it serves as a binding platform for procaspases, inhibits their activation and apoptosis, and thereby regulates neutrophil survival [3]. We have shown that high levels of cytosolic PCNA are found in multiple myeloma cells, and that targeting PCNA with APIM-peptide induces rapid caspase activation (caspases 3,7, 8 and 9) followed by apoptosis in multiple myeloma, but not in healthy primary cells [4]. Recently, cytosolic PCNA was shown to bind and stabilize procaspase-9 in a neuroblastoma cell line, and interestingly S-nitrosylation of PCNA blocked this interaction suggesting that the binding is regulated by posttranslational modifications (PTMs) [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in mature non-proliferating neutrophils, PCNA is exclusively located in the cytosol where it serves as a binding platform for procaspases, inhibits their activation and apoptosis, and thereby regulates neutrophil survival [3]. We have shown that high levels of cytosolic PCNA are found in multiple myeloma cells, and that targeting PCNA with APIM-peptide induces rapid caspase activation (caspases 3,7, 8 and 9) followed by apoptosis in multiple myeloma, but not in healthy primary cells [4]. Recently, cytosolic PCNA was shown to bind and stabilize procaspase-9 in a neuroblastoma cell line, and interestingly S-nitrosylation of PCNA blocked this interaction suggesting that the binding is regulated by posttranslational modifications (PTMs) [5].…”
Section: Introductionmentioning
confidence: 99%
“…We found that overexpression of the APIM-peptide, or treatment of cells with an APIM-containing cell penetrating peptide, reduced growth rate and increased apoptosis when cancer cells were exposed to chemotherapeutics and/or were stressed, but not, or far less, under normal conditions. Furthermore, a peptide with an impaired APIM-sequence, mutAPIM-peptide, had less effect, thus the APIM-PCNA interaction is required for these activities [4,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…S2). 13,31 In particular, it has been reported that both the PL and p21 peptides interfere with DNA replication. 13,19 The results presented here outline a general strategy to design and efficiently deliver these functional peptides using cell-penetrating peptides providing a versatile tool to potentially target proliferative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…We did site directed mutagenesis in the TbPCNA and HsPCNA open reading frames, changing methionine-40 to alanine (M40A) in both homologs. M40 is part of the evolutionary conserved central loop that forms the hydrophobic pocket of PCNA with the IDCL and the C-terminus (CarrascoMiranda et al, 2014;Tsurimoto and Stillman, 1991;Warbrick et al, 1995) to mediate hydrophobic interactions with PIP-box proteins (Muller et al, 2013). We discovered that parasites overexpressing either the TbPCNA M40A mutant (Figure 2 To test this hypothesis, we used the small molecule inhibitor T2AA as the chemical tool to broadly inhibit PCNA/PIP-box protein interactions.…”
Section: Specific Inhibition Of Stable Pcna/pip-box Protein Interactimentioning
confidence: 99%